Inhibition of a specific antimalarial molecular target and correlation with the activity against p. falciparum as selection criteria of potential antimalarials from natural sources (2006)
ABSTRACT: Malaria is the world's most important parasitic infection, ranking among the major health and developmental challenges for the poor countries of the world (1). It is a disease caused by parasites of the genus Plasmodium and it is the responsible of almost 2.7 millions of deaths each year. One of the different strategies in order to find new treatment alternatives is using the pharmacological knowledge available about mechanism of action of antimalarials available, as well as potential targets to be attacked in the discovery of new molecular entities from our biodiversity. In this work two species of Colombian flora were studied, Monnina angustata (Polygalaceae) and Symbolanthus pterocalyx (Gentianaceae), these species have restricted growing in Colombia and its biogeography limits. A bioguided study was developed according to which the chemical fractionation was carried out looking for the ability for inhibit β-hematin formation, synthetic substance identical to hemozoin which is formed inside the food parasitic vacuole as heme detoxification strategy. The inhibition of the β-hematin formation triggers oxidative stress process mediated by monomeric and dymerics forms of ferriprotoporphirin IX that results in highly toxic effects for parasite. This model was used in order to determine the inhibition percentage and that IC50 of extracts and fractions compared against chloroquine. Finally, the activity of the fractions which were inhibitor of β- hematin formation was correlated with other model that allow make a radioisotope determination of cellular viability using FCB-1 strain of P. falciparum cultured in presence of radiolabeled hypoxanthine. It was obtained an important correlation between the activity against the molecular target and on the parasite (rp=0.7186, valor P*).